Análise das alternativas, dificuldades e limitações à expansão das receitas próprias dos municípios da região do Vale do Rio Pardo – RS - Ravanello, Mariângela (2018)
The moment of economic instability imposes ever greater challenges on the management of municipalities, directly interfering with the tax collection of all federal entities, impacting doubly on the municipalities, both in own revenues and in revenues from constitutional transfers, especially the FPM that reaches represent 70% of the collection. A scenario that subsidized the objective of the work to analyze alternatives for the expansion of the own collection of the municipalities of the COREDE region of Vale do Rio Pardo, from 2009 to 2016. Methodologically, this is a descriptive, quantitative-qualitative research whose method of approach is analytical-comparative. To promote the analysis, the municipalities were stratified according to the population range in three distinct groups: groups 2 and 3, population less than 50,000 inhabitants, economic activity not expressive, basically rural; high degree of dependence of the MPF, average of 28 and 41% respectively in the period; a small share in own collection of 2.52 and 5.35%; precarious organizational structure of the tax sector, with a unique cadre of professionals. Group 1, with a population of more than 50,000 who are more economically structured with an inverse relationship of dependence of FPM, average in the period of 15%, own collection reached the average of 11.68%. The results confirm the need for municipalities to develop actions that aim to increase own revenues and, consequently, result in improvements in the supply of public goods and services, such as the electronic invoice implemented by a large group of municipalities as an alternative for control and inspection of the ISS collection.